Empowered Maryam Bint ‘Imrān: An Intertextual Study of the Qur’an and the Bible - Rifa Tsamrotul Syaadah; Iqrimah Azhari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
Women’s empowerment has been a crucial aspect of Indonesia’s national development since 1978 year, yet accessibility challenges in rural areas persist. This research aims to explore the figure of Maryam as a theological model for women’s empowerment through a comparative analysis of the Qur’an and the Bible. Employing a qualitative method with an intertextual approach, this study integrates classical and contemporary exegesis, including the perspectives of al-Ṭabarī, Ibn Kathīr, and Quraish Shihab, with selected Biblical texts. The findings indicate that both religious traditions position Maryam as a figure of high spiritual authority and moral integrity. In the Qur’an, Maryam is portrayed as a resilient woman facing social pressure with moral courage, while in the Bible (Luke 1:26-38), she is presented as an independent figure actively contributing to the prophetic mission. This study concludes that Maryam is not merely a historical-religious figure but a universal symbol of women’s empowerment that transcends dogmatic boundaries. The implications of these findings contribute to contemporary discourses on gender and religion, while positioning Maryam as a strategic point of convergence in interfaith dialogue. Through her exemplary moral steadfastness and spiritual independence, Maryam offers a new paradigm for strengthening women’s roles in both public and domestic spheres.